Virulence and antimicrobial resistance of Klebsiella pneumoniae isolated from passerine and psittacine birds. Issue 2 (3rd March 2016) - Davies, Y. M.; Cunha, M. P. V.; Oliveira, M. G. X.; Oliveira, M. C. V.; Philadelpho, N.; Romero, D.C.; Milanelo, L.; Guimarães, M. B.; Ferreira, A. J. P.; Moreno, A. M.; Sá, L. R. M.; Knöbl, T.
ABSTRACT: Klebsiella pneumoniae is considered one of the most important Gram-negative opportunistic pathogens. The contact between humans and birds poses health risks to both. The aim of this study was to investigate the resistance and virulence of K. pneumoniae isolates from psittacines and passerines, seized from illegal trade in Brazil. We analysed 32 strains isolated from birds of the orders Psittaciformes and Passeriformes by polymerase chain reaction (PCR) for virulence factor genes. Antibiotic resistance was assessed by disk diffusion assay and PCR. The results indicated that fimH (100%), uge (96.8%), kfu (81.2%) and irp -2 (68.7%) were the most common virulence genes, followed by kpn (46.8%), K2 (43.7%), mrkD (34.3%) and iroN (15.6%). The combination of virulence genes resulted in a great diversity of genotypes and the heterogeneity of the strains is also confirmed in the analysis by amplified fragment length polymorphism. The susceptibility profiles of the K. pneumoniae showed 25% of multiple antibiotic resistance strains. We identified seven strains that presented non-extended spectrum beta lactamase bla SHV variants SHV-1 and SHV-11 and one strain positive to the bla TEM-1 gene. Plasmid-mediated quinolone resistance was present in 10 strains (10/32). The data obtained in this study reveal the pathogenic potential of this pathogen and highlight the need for surveillance and monitoring.